On the Statistical Estimation of Parametric Frontier Production Functions: Rejoinder - Schmidt, Peter (The Review of Economics and Statistics, 1978)
assumptions in each individual case, and often a modification of the classical model may become necessary. On the other hand, for any research in which the frontier function is important, the programming methodology is probably a more relevant tool. True, the sampling properties of the programming estimators are mostly unknown. But with the development of modern computer technology, large scale simulation studies can be expected to ascertain the sampling properties under various assumptions. It is the hope of this author that reports about results of such simulation studies will appear in the literature in the near future.